LOCAL SUSTAINABLE DEVELOPMENT AND PUBLIC-PRIVATE PARTNERSHIP: THE CASE OF CITY LOGISTICS IN NOLA (ITALY) - Zaric, Sinisa (Poslovna ekonomija, 2018)
The research is focused on one of the most important urban problems: reducing the carbon emission in the city centers, mainly on its economic dimension. Apart from the more general problem of creating a green transportation system, there is a special need for city centers development in the context of urban sustainability. Bringing the retail and tourism businesses back to the city centers could revitalize the central areas that are, either abandoned or making less contributions to the well-being of the citizens. Creating pedestrian zones plays the main role of sustainable development, contributing to its three dimensions: social, economic and environmental. It is not rare that the economic dimensions of this type of projects give evidences of the projects’ vulnerability. The case studies and literature give evidences of the problems in achieving sustainability of the partnerships with businesses and possibilities of public-private partnership, in general. The research is based on comparative analyses of city logistics in European countries. The case study illustrates the problems of introducing the PPP in the field of urban distribution in the historical city of Nola (Italy).